The phase of pre‐stimulus brain oscillations correlates with cross‐modal synchrony perception. (24th October 2018) - Ikumi, Nara; Torralba, Mireia; Ruzzoli, Manuela; Soto‐Faraco, Salvador
Abstract: In everyday life multisensory events, such as a glass crashing on the floor, the different sensory inputs are often experienced as simultaneous, despite the sensory processing of sound and sight within the brain are temporally misaligned. This lack of cross‐modal synchrony is the unavoidable consequence of different light and sound speeds, and their different neural transmission times in the corresponding sensory pathways. Hence, cross‐modal synchrony must be reconstructed during perception. It has been suggested that spontaneous fluctuations in neural excitability might be involved in the temporal organisation of sensory events during perception and account for variability in behavioural performance. Here, we addressed the relationship between ongoing brain oscillations and the perception of cross‐modal simultaneity. Participants performed an audio‐visual simultaneity judgement task while their EEG was recorded. We focused on pre‐stimulu activity, and found that the phase of neural oscillations at 13 ± 2 Hz 200 ms prior to the stimulus correlated with subjective simultaneity of otherwise identical sound‐flash events. Remarkably, the correlation between EEG phase and behavioural report occurred in the absence of concomitant changes in EEG amplitude. The probability of simultaneity perception fluctuated significantly as a function of pre‐stimulus phase, with the largest perceptual variation being accounted for phase angles nearly 180º apart. This pattern was strongly reliable for sound‐flash pairs but not for flash‐sound pairs. Overall, these findings suggest that the phase of ongoing brain activity might underlie internal states of the observer that influence cross‐modal temporal organisation between the senses and, in turn, subjective synchrony. Abstract : In this study, we measured EEG activity while participants performed a simultaneity judgement task on simple flash‐sound pairs. We demonstrated that the probability of simultaneity perception fluctuates as a function of pre‐stimulus phase. Specifically, we found a relationship between the oscillatory phase at 13 ± 2 Hz, 200 ms pre‐stimulus and the modulations in simultaneous/non‐simultaneous (S/NS) proportion of percepts for sound‐flash pairs but not for flash‐sound pairs. Interestingly, mean group phases for simultaneous (S, blue vertical line) and non‐simultaneous (NS, red vertical line) perception were nearly opposite (180° difference). Overall, these findings suggest that the phase of ongoing brain activity might underlie internal states of the observer that influence cross‐modal temporal organisation between the senses and, in turn, subjective synchrony.